Dermatofibrosarcoma protuberans of perianal region: a rare case report - Shanmugam, Subbiah; Bharath, Radha Siva (International Surgery Journal, 2022)
Dermatofibrosarcoma protuberans (DFSP) is a rare locally aggressive slow growing soft tissue sarcoma with very low metastatic potential with high local recurrence rates. We presented a rare case of DFSP of left perianal region ulcerating into anal canal, we did wide excision with 3 cm margin along with abdominoperineal excision of rectum and permanent colostomy, defect is reconstructed with left pedicled antero-lateral thigh flap. DFSP has high chance of recurrence, it should be excised with at least 2-3 cm 3D margin and patient should be followed up for a long time.